Entropic analysis: understanding economic sector relationships with Leontief’s input-output tables - Kharatyan, Alvard; Asatryan, Vahe; Shakhanumyan, Svetlana (Bulletin of Yerevan University G: Economics, 2024)
The article delves into the evolution of the "entropy" concept and its corresponding theoretical interpretations. Employing Shannon’s entropy formula and leveraging the methodology of entropy calculation through Leontief’s input-output tables, the study conducts entropy calculations for the economic systems of Australia, the Republic of South Africa, the United States, Luxembourg, Russia, South Korea, Japan, India, and China. These calculations are based on the tables published by the Organization for Economic Cooperation and Development. The primary finding of the study can be summarized as follows: Economic entropy, determined through the coefficients of total costs in Leontief’s input-output tables, serves as a gauge of the interconnectedness among various branches within the economic system. Furthermore, financial and economic crises, as well as natural disasters, contribute to an escalation in the interconnectedness of economic branches, signifying a rise in entropy.